Evaluation of Expression and Association of ER, PR and Ki67 Tumour Markers in Carcinoma Breast (Journal of National Institute of Neurosciences Bangladesh, 2024)
Background: Several factors contribute to determine tumor prognosis and treatment strategies of breast cancer patients. Use of hormone receptor are relatively new and have proven its efficacy.Objective: The purpose of the present study was to evaluate the expression and association of ER, PR and Ki67 tumor markers in carcinoma breast patients.Methodology: In this analytical cross-sectional study, fifty-two adult cases of carcinoma breast with tru-cut biopsy underwent breast conservative surgery (BCS) or mastectomy in the Department of Surgery at Sir Salimullah Medical College and Mitford Hospital. This study excluded patients who had received neoadjuvant therapy, had recurrent breast carcinoma, had extensive metastasis, or had advanced breast carcinoma. Each participant signed an informed written consent form. Demographic information, a detailed history, and a clinical examination were all obtained. All samples were examined histopathologically and immunohistochemically. The immunohistochemistry report was used to collect biomarker data. The relationship between ER, PR, and Ki67 and histopathological findings was then investigated. SPSS 12.0 was used to analyse the collected data.Results: Half of the patients belonged to age group 51 to 60 years (50%). Majority respondents were from rural area (65%) and maximum were poor (57.7%). Majority respondents were T2 (48.1%) stage of tumor size followed by Tl (36%) and T3 (15.4%). According to histological grading, 44.2% had Grade II tumour, 38.5% had Grade I tumour and 17.3% had Grade III tumour. Among the respondents 80.8% had ductal carcinoma followed by decreasing order 15.4% had lobular carcinoma and 3.8% had others types of carcinoma. Regarding lymph node status, 30.8% had N1 stage lymph node involvement followed 28.8% had N2 stage lymph node involvement 26.9% had N0 stage lymph node involvement and 13.5% had N3 stage lymph node involvement. Among the respondents 65.4% had L0 and 34.6% had LI stage of lymphatic invasion. Moreover, 78.8% had V0 stage vascular invasion and 21.2% had V1 stage vascular invasion. Of the patients, 44.2% had both ER and PR negative and 17.3% had both ER and PR positive. ER positive was found significantly higher among grade I carcinoma, PR positive was found significantly higher among grade I carcinoma and Ki67 was found significantly lower in grade I carcinoma. Among the patient's results had been found significant, ER positivity and PR positivity decline with higher lymph node staging whereas direct relation was present with Ki67. There's a significant decline in ER positivity and PR positivity with lymphatic invasion, but not with Ki67. ER and PR positivity declined with vascular invasion, whereas there was a direct correlation between Ki67 and vascular invasion.Conclusion: Higher grading, higher lymph node staging, and lymphovascular invasion result in a decline in ER and PR positivity, whereas Ki67 showed a direct correlation. Journal of National Institute of Neurosciences Bangladesh, July 2023;9(2):116-121